Coping mechanisms of abused women - Egot, Aileen Joy C.
This examines the different individual and institutional coping mechanisms employed by six battered women of Davao City and Monkayo, Compostela Valley Province. The individual coping mechanisms were categorized into two types; the problem-focused and emotion-focused. Meanwhile, the formal institutions that may intervene in the abusive relationship are; government organizations, local government units, non-government organizations, people's organizations, police force and others. The respondents for this study were six women who were physically, psychologically, verbally, economically and sexually abused by their husbands or live-in partners. Three of which were official clients and under the protection of the Department of Social Welfare and Development- Substitute Home Care for Women located at the City Jail Road, Maa, Davao City, while the other three respondents were recommended by the personal contacts of the researcher. The researcher used the case study method. The data were collected through personal one-on-one interviews and case conferences with the case managers of DSWD-SHCW. The researcher used as guide questionnaire in which the questions were mostly open-ended. The survivor theory (Gondolf and Fisher, 1988) was used as the theoretical framework of this study. This approach is consistent with the view that abused women are active decision makers who constantly employ coping mechanisms which they think as appropriate to their circumstances. These six abused women had employed similar and different individual coping mechanisms. Most of the respondents had employed emotion-focused individual coping mechanisms. Only two of them had used the confrontive problem-focused coping mechanism. This shows that the abused women were more likely to focus more on dealing with their emotions rather than with their objectivity in analyzing the kind of coping ,mechanisms appropriate in their respective situations. All of the respondents were able to ask for institutional intervention. They had either gone to their barangay councils, to local police stations or to a temporary shelter (DSWD-SHCW).
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao